2023
DOI: 10.1111/imr.13292
|View full text |Cite
|
Sign up to set email alerts
|

The discovery of NLRP3 and its function in cryopyrin‐associated periodic syndromes and innate immunity

Christopher D. Putnam,
Lori Broderick,
Hal M. Hoffman

Abstract: SummaryFrom studies of individual families to global collaborative efforts, the NLRP3 inflammasome is now recognized to be a key regulator of innate immunity. Activated by a panoply of pathogen‐associated and endogenous triggers, NLRP3 serves as an intracellular sensor that drives carefully coordinated assembly of the inflammasome, and downstream inflammation mediated by IL‐1 and IL‐18. Initially discovered as the cause of the autoinflammatory spectrum of cryopyrin‐associated periodic syndrome (CAPS), NLRP3 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 173 publications
0
1
0
Order By: Relevance
“…When th central protein NLRP3 is stimulated by activation signals, ASC interacts with the PYD o NLRP3 via homotypic PYD, followed by recruiting pro-caspase-1 with CARD-CARD in teractions, resulting in inflammasome oligomerization (Figure 1) [35]. Then, pro-caspase 1 cleaves itself into active caspase-1, which subsequently mediates pro-IL-1β, pro-IL-18 and GSDMD to cleave into active subunits, triggering pyroptosis and inflammation [36] Due to its ability to be activated by manifold types of pathogens or danger signals, NLRP inflammasome can play a pivotal role in various disease processes, namely, cryopyrin associated periodic syndromes (CAPS) [37,38], Alzheimer's disease [39], rheumatoid ar thritis [40], and others [41]. Additionally, many studies have suggested a correlation be tween NLRP3 inflammasome and AAA in recent years.…”
Section: Nlrp3 Inflammasome In Aaamentioning
confidence: 99%
“…When th central protein NLRP3 is stimulated by activation signals, ASC interacts with the PYD o NLRP3 via homotypic PYD, followed by recruiting pro-caspase-1 with CARD-CARD in teractions, resulting in inflammasome oligomerization (Figure 1) [35]. Then, pro-caspase 1 cleaves itself into active caspase-1, which subsequently mediates pro-IL-1β, pro-IL-18 and GSDMD to cleave into active subunits, triggering pyroptosis and inflammation [36] Due to its ability to be activated by manifold types of pathogens or danger signals, NLRP inflammasome can play a pivotal role in various disease processes, namely, cryopyrin associated periodic syndromes (CAPS) [37,38], Alzheimer's disease [39], rheumatoid ar thritis [40], and others [41]. Additionally, many studies have suggested a correlation be tween NLRP3 inflammasome and AAA in recent years.…”
Section: Nlrp3 Inflammasome In Aaamentioning
confidence: 99%